Pengaruh Profitabilitas, Likuiditas, Leverage Dan Ukuran Perusahaan Terhadap Financial Distress - Astri Fitria; Nenny Syahrenny (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2022)
This research aimed to observe the manufacturing company listed on Indonesia Stock Exchange (IDX) in the 2014-2020 periods, to predict the company which had financial distress with several variables which were profitability, liquidity, leverage, firm size and financial distress. Based on the purposive sampling it obtained 13 companies by criteria i.e. 91 samples. Furthermore, this research used secondary data which was obtained from the official website of the Indonesia Stock Exchange (IDX) i.e. www.idx.co.id. Moreover, this research used logistic regressions analysis with data processing application program SPSS (Statistical Package Social Sciences) 25 version. The result of this research indicated that: (1) the profitability variable measured by return on equity had a negative effect on the financial distress, (2) the liquidity variable measured by the current ratio did not have any effect on the financial distress, (3) the leverage variable measured by debt to asset had a positive effect on the financial distress, (4) the firm size variable measured by log total did not have any effect on financial distress.